Front Cover: Bio‐Based Cycloalkanes: The Missing Link to High‐Performance Sustainable Jet Fuels (ChemSusChem 22/2020). Issue 22 (27th October 2020) - Muldoon, Jake A.; Harvey, Benjamin G.
Abstract : The Front Cover shows a variety of high‐energy‐density cycloalkanes that can be produced from bio‐based substrates. These molecules have applications as components of high‐performance jet fuels, which exhibit improved performance and dramatically decreased net greenhouse gas emissions compared to petroleum‐derived jet fuels. The study of high‐throughput catalytic routes for the upgrading of biomass feedstocks to cycloalkanes holds great promise for sustainable aviation. More information can be found in the Review by J. A. Muldoon and B. G. Harvey .